Phytochemistry Screening and Antioxidant Activities of Extract Pomegranate, Grape, Fig, and Olive in the Various Solvent - Evika Sandi Savitri; Kholifah Holil; Ruri Siti Resmisari (Jurnal Biodjati, 2022)
The active compounds of grape, pomegranate, olive, and fig have anthocyanins that potential as antioxidant are flavonoids. Flavonoids have potential as antioxidant  to prevent and therapy various oxidative stress and related diseases. This study aimed to examine the antioxidant activity of a combination of pomegranate, grape, fig, and olive extracts using the DPPH (diphenyl-2-picrylhydrazyl) method.  The maceration method used was maceration of dry Simplicia with methanol 95% solvent, fresh maceration with 95% methanol and dry Simplicia with 95% ethanol solvent. The results of the phytochemistry test showed several compounds found in the extract combination pomegranate, grapes, fig, and olives such as polyphenol, flavonoid, tannin, steroid/triterpenoid. The result of the antioxidant test showed the fresh maceration 95% methanol showed higher results with the IC50 of 25.22 with a potent antioxidant activity category.